A rubber-type lithium battery pressure-sensitive adhesive tape

By using natural rubber and homemade crosslinking agent, the prepared rubber-type lithium battery pressure-sensitive adhesive tape solves the problem of poor performance stability in the prior art, and achieves the improvement of high peel strength and high temperature resistance.

CN116355543BActive Publication Date: 2025-02-11HUNAN YOUDUO NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310427897.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-20
Publication Date
2025-02-11
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

The existing lithium battery pressure-sensitive adhesive tape has poor performance stability in extreme lithium battery electrolyte environments and cannot meet the increasing performance requirements of lithium batteries.

Method used

Natural rubber is used as the main elastomer, and rubber-type lithium battery pressure-sensitive adhesive tape is prepared through homemade crosslinking agent A and crosslinking agent B to improve its peel strength and high temperature resistance.

Benefits of technology

The peel strength and high temperature resistance of rubber-type lithium battery pressure-sensitive adhesive tape are significantly improved, and its comprehensive performance is optimized.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a rubber-type lithium battery pressure-sensitive adhesive tape, the preparation method of which is as follows: (1) preparing a crosslinking agent A; (2) preparing a crosslinking agent B; (3) plasticizing natural rubber in an open mill, shredding and dissolving in toluene after plasticizing, then adding the crosslinking agent A, crosslinking agent B and an antioxidant, stirring evenly, adding toluene to adjust the viscosity, coating on a PET film, and baking at 130° C. to obtain the rubber-type lithium battery pressure-sensitive adhesive tape. The method of the present invention uses natural rubber as the main elastomer, and by adding the homemade crosslinking agent of the present invention, the prepared adhesive tape has high peel strength and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesive materials, and in particular to a rubber-type lithium battery pressure-sensitive adhesive tape. Background Art

[0002] Lithium battery pressure-sensitive adhesive tape is mainly used in the insulation protection of battery tabs during the production of lithium batteries, the insulation protection and packaging fixation of the positive and negative leads and circuits outside the battery cell, the insulation fixation of the terminal of the battery cell, and the prevention of electrolyte leakage, etc. Therefore, the adhesive tape needs to have suitable viscosity and be able to maintain stable performance in extreme lithium battery electrolyte environments. At present, the domestic lithium battery pressure-sensitive adhesive tape market is still dominated by polyacrylate adhesive tapes, but because its performance cannot meet the increasingly high performance requirements of lithium batteries for adhesive tapes, it still has certain shortcomings. The high viscoelasticity and low polarity of natural rubber can make the performance of pressure-sensitive adhesives less affected by lithium battery electrolytes, and maintain excellent performance in electrolytes. Therefore, rubber type will be a hot spot in the application research of lithium battery pressure-sensitive adhesives. Summary of the invention

[0003] To this end, the present invention provides a rubber-type lithium battery pressure-sensitive adhesive tape, and the preparation method thereof is as follows:

[0004] (1) polycarbonate diol and N-methylpyrrolidone are mixed to form a mixture, the mixture is stirred, epichlorohydrin is added to the mixture under stirring, and after the addition is completed, the temperature is kept constant at 50±3° C. in a water bath, and after the temperature reaches the temperature, boron trifluoride ether is added to the mixture, and the mixture is kept warm for 120 to 150 minutes after the addition, and after the insulation is completed, sodium hydroxide solution is added to the mixture, and the mixture is kept warm in a water bath at 50±3° C. for 120 to 150 minutes, and then air-cooled to room temperature, ethyl acetate is added for extraction, the aqueous phase is removed, and then the ethyl acetate is removed by rotary evaporation to obtain a crosslinking agent A;

[0005] (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for more than 2 hours, and then methyl ethyl ketoxime is added to the mixed solution. After the addition is completed, the temperature is continued to be kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm, and refluxed for more than 3 hours. The mixed solution is then air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is then added dropwise to the mixed solution, and after the addition is completed, the temperature is kept constant at 50±3°C in a water bath, and the mixture is kept warm for more than 40 minutes. Then, N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm at a temperature range of 50±3°C for more than 60 minutes. Then, p-methoxyphenol is added to the mixture to obtain a crosslinking agent B;

[0006] (3) The natural rubber is plasticized in an open mixing mill, and after plasticization, it is chopped and dissolved in toluene, and then the cross-linking agent A, the cross-linking agent B and the antioxidant are added, and stirred evenly. After adding toluene to adjust the viscosity, it is coated on a PET film and baked at 130° C. to obtain the rubber-type lithium battery pressure-sensitive adhesive tape.

[0007] Furthermore, the mixing ratio of the polycarbonate diol and N-methylpyrrolidone is polycarbonate diol: N-methylpyrrolidone = 4-6 g / 100 mL; the mass ratio of the added epichlorohydrin and boron trifluoride ether to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 10-14 g: 0.05-0.06 g: 4-6 g.

[0008] Furthermore, the concentration of the sodium hydroxide solution is 40-50 g / L, and the solvent is water; the mass ratio of the added amount of the sodium hydroxide solution to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50 mL: 4-6 g.

[0009] Furthermore, the mass ratio of the toluene diisocyanate trimer and acetone is toluene diisocyanate trimer: acetone = 8-10: 150; the mass ratio of the added polyethylene glycol monomethyl ether and methyl ethyl ketoxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketoxime: toluene diisocyanate trimer = 4-6: 0.8-1.2: 8-10.

[0010] Furthermore, the mass ratio of 3-aminopropyltriethoxysilane added dropwise to the mixed liquid is 3-aminopropyltriethoxysilane: mixed liquid = 6-9:50; the mass ratio of the added mass of the N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass ratio of the 3-aminopropyltriethoxysilane is N,N-dimethylethanolamine: 1,3-propane sultone: p-methoxyphenol: 3-aminopropyltriethoxysilane = 0.15-0.25: 0.3-0.4: 0.03-0.06: 6-9.

[0011] Furthermore, in the coating liquid, the rubber, crosslinking agent A, crosslinking agent B and antioxidant after mastication are calculated by weight as follows: 100 parts of rubber, 1-2 parts of crosslinking agent A, 0.2-0.4 parts of crosslinking agent B, and 3-5 parts of antioxidant.

[0012] The beneficial effects of the present invention are as follows: the method of the present invention uses natural rubber as the main elastomer, and by adding the homemade cross-linking agent of the present invention, the prepared adhesive tape has higher peel strength and high temperature resistance, and optimizes the comprehensive performance of the rubber-type lithium battery pressure-sensitive adhesive tape. DETAILED DESCRIPTION

[0013] The present invention will be further described below in conjunction with the embodiments.

[0014] Example 1

[0015] A rubber-type lithium battery pressure-sensitive adhesive tape, the preparation method of which is as follows:

[0016] (1) polycarbonate diol and N-methyl pyrrolidone are mixed to form a mixture, wherein the mixing ratio of the polycarbonate diol and the N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 4 g / 100 mL; the mixture is stirred, and epichlorohydrin is added to the mixture under stirring. After the addition is completed, the mixture is kept in a water bath at a constant temperature of 50±3° C., and after the temperature reaches 50±3° C., boron trifluoride etherate is added to the mixture, and the mixture is kept incubated for 120 minutes. After the incubation is completed, a sodium hydroxide solution is added to the mixture, and the concentration of the sodium hydroxide solution is 40 g / L, the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 4g; continue to keep warm in a water bath at 50±3°C for 120min, then air cool to room temperature, extract with ethyl acetate, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; wherein the mass ratio of the epichlorohydrin and boron trifluoride ether added to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 10g: 0.05g: 4g;

[0017] (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, wherein the mass ratio of toluene diisocyanate trimer to acetone in the mixed solution is toluene diisocyanate trimer: acetone = 8:150; polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for 2 hours, and then methyl ethyl ketone oxime is added to the mixed solution, wherein the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 4:0.8:8; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for 3 hours, and then the mixed solution is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxy is then added dropwise to the mixed solution; Silane, 3-aminopropyltriethoxysilane is added dropwise to the mixed solution at a mass ratio of 3-aminopropyltriethoxysilane: mixed solution = 6:50; after the addition is completed, the water bath is kept constant at 50±3°C and kept warm for 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture to obtain a crosslinking agent B; wherein the mass ratio of the added mass of N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass of the 3-aminopropyltriethoxysilane is N,N-dimethylethanolamine:1,3-propane sultone:p-methoxyphenol:3-aminopropyltriethoxysilane=0.15:0.3:0.03:6;

[0018] (3) The natural rubber is plasticized in an open mill, and after plasticization, it is chopped and dissolved in toluene, and then the crosslinking agent A, crosslinking agent B and antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, crosslinking agent A, crosslinking agent B and antioxidant in the coating liquid are calculated by weight as follows: 100 parts of rubber, 1 part of crosslinking agent A, 0.4 parts of crosslinking agent B, and 3 parts of antioxidant (KY-405); after coating, the rubber is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm).

[0019] Example 2

[0020] A rubber-type lithium battery pressure-sensitive adhesive tape, the preparation method of which is as follows:

[0021] (1) polycarbonate diol and N-methyl pyrrolidone are mixed to form a mixture, wherein the mixing ratio of the polycarbonate diol and the N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 5 g / 100 mL; the mixture is stirred, and epichlorohydrin is added to the mixture under stirring. After the addition is completed, the mixture is kept in a water bath at a constant temperature of 50±3° C., and after the temperature reaches 50±3° C., boron trifluoride etherate is added to the mixture, and the mixture is kept incubated for 120 minutes. After the incubation is completed, a sodium hydroxide solution is added to the mixture, and the concentration of the sodium hydroxide solution is 40 g / L, the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 5g; continue to keep warm in a water bath at 50±3°C for 120min, then air cool to room temperature, extract with ethyl acetate, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; wherein the mass ratio of the epichlorohydrin and boron trifluoride ether added to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 12g: 0.05g: 5g;

[0022] (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, wherein the mass ratio of toluene diisocyanate trimer to acetone in the mixed solution is toluene diisocyanate trimer: acetone = 9:150; polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for 2 hours, and then methyl ethyl ketone oxime is added to the mixed solution, wherein the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 5:1:9; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for 3 hours, and then the mixed solution is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is then added dropwise to the mixed solution; alkane, and 3-aminopropyltriethoxysilane is added dropwise to the mixed solution at a mass ratio of 3-aminopropyltriethoxysilane: mixed solution = 7:50; after the addition is completed, the water bath is kept at a constant temperature of 50±3°C and kept warm for 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture to obtain a crosslinking agent B; wherein the mass ratio of the added mass of N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass of the 3-aminopropyltriethoxysilane is N,N-dimethylethanolamine:1,3-propane sultone:p-methoxyphenol:3-aminopropyltriethoxysilane=0.2:0.3:0.04:7;

[0023] (3) The natural rubber is plasticized in an open mill, and after plasticization, it is chopped and dissolved in toluene, and then the cross-linking agent A, the cross-linking agent B and the antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, the cross-linking agent A, the cross-linking agent B and the antioxidant in the coating liquid are calculated by weight as follows: 100 parts of rubber, 1 part of cross-linking agent A, 0.3 parts of cross-linking agent B, and 4 parts of antioxidant (KY-405); after coating, the rubber is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm).

[0024] Example 3

[0025] A rubber-type lithium battery pressure-sensitive adhesive tape, the preparation method of which is as follows:

[0026] (1) polycarbonate diol and N-methyl pyrrolidone are mixed to form a mixture, wherein the mixing ratio of the polycarbonate diol and the N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 5 g / 100 mL; the mixture is stirred, and epichlorohydrin is added to the mixture under stirring. After the addition is completed, the mixture is kept in a water bath at a constant temperature of 50±3° C., and after the temperature reaches 50±3° C., boron trifluoride etherate is added to the mixture, and the mixture is kept incubated for 120 minutes. After the incubation is completed, a sodium hydroxide solution is added to the mixture, and the concentration of the sodium hydroxide solution is 40 g / L, the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 5g; continue to keep warm in a water bath at 50±3°C for 120min, then air cool to room temperature, extract with ethyl acetate, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; wherein the mass ratio of the epichlorohydrin and boron trifluoride ether added to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 13g: 0.06g: 5g;

[0027] (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, wherein the mass ratio of toluene diisocyanate trimer to acetone in the mixed solution is toluene diisocyanate trimer: acetone = 9:150; polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for 2 hours, and then methyl ethyl ketone oxime is added to the mixed solution, wherein the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 5:1:9; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for 3 hours, and then the mixed solution is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is then added dropwise to the mixed solution; alkane, and 3-aminopropyltriethoxysilane is added dropwise to the mixed solution at a mass ratio of 3-aminopropyltriethoxysilane: mixed solution = 8:50; after the addition is completed, the water bath is kept at a constant temperature of 50±3°C and kept warm for 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture to obtain a crosslinking agent B; wherein the mass ratio of the added mass of N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass of the 3-aminopropyltriethoxysilane is N,N-dimethylethanolamine:1,3-propane sultone:p-methoxyphenol:3-aminopropyltriethoxysilane=0.2:0.4:0.05:8;

[0028] (3) The natural rubber is plasticized in an open mill, and after plasticization, it is chopped and dissolved in toluene, and then the crosslinking agent A, crosslinking agent B and antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, crosslinking agent A, crosslinking agent B and antioxidant in the coating liquid are calculated by weight as follows: 100 parts of rubber, 2 parts of crosslinking agent A, 0.3 parts of crosslinking agent B, and 4 parts of antioxidant (KY-405); after coating, it is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm).

[0029] Example 4

[0030] A rubber-type lithium battery pressure-sensitive adhesive tape, the preparation method of which is as follows:

[0031] (1) polycarbonate diol and N-methyl pyrrolidone are mixed to form a mixture, wherein the mixing ratio of the polycarbonate diol and the N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 6 g / 100 mL; the mixture is stirred, and epichlorohydrin is added to the mixture under stirring. After the addition is completed, the mixture is kept in a water bath at a constant temperature of 50±3° C., and after the temperature reaches 50±3° C., boron trifluoride etherate is added to the mixture, and the mixture is kept incubated for 120 minutes. After the incubation is completed, a sodium hydroxide solution is added to the mixture, and the concentration of the sodium hydroxide solution is 40 g / L, the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 6g; continue to keep warm in a water bath at 50±3°C for 120min, then air cool to room temperature, extract with ethyl acetate, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; wherein the mass ratio of the epichlorohydrin and boron trifluoride ether added to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 14g: 0.06g: 6g;

[0032] (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, wherein the mass ratio of toluene diisocyanate trimer to acetone in the mixed solution is toluene diisocyanate trimer: acetone = 10:150; polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for 2 hours, and then methyl ethyl ketone oxime is added to the mixed solution, wherein the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime added to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 6:1.2:10; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for 3 hours, and then the mixed solution is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxycarbonyl is added dropwise to the mixed solution, and the mixture is stirred, kept warm for 3 hours, and then the mixture is cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxycarbonyl is added dropwise to the mixed solution, and the mixture is cooled to room temperature, and the acetone is removed by rotary evaporation. 1,3-propane sultone, and 3-aminopropyl triethoxysilane is added dropwise to the mixed solution in a mass ratio of 3-aminopropyl triethoxysilane: mixed solution = 9:50; after the addition is completed, the water bath is kept constant at 50±3°C and kept warm for 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture to obtain a crosslinking agent B; wherein the mass ratio of the added N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass ratio of the 3-aminopropyl triethoxysilane is N,N-dimethylethanolamine:1,3-propane sultone:p-methoxyphenol:3-aminopropyl triethoxysilane=0.25:0.4:0.06:9;

[0033] (3) The natural rubber is plasticized in an open mill, and after plasticization, it is chopped and dissolved in toluene, and then the crosslinking agent A, crosslinking agent B and antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, crosslinking agent A, crosslinking agent B and antioxidant in the coating liquid are calculated by weight as follows: 100 parts of rubber, 2 parts of crosslinking agent A, 0.2 parts of crosslinking agent B, and 5 parts of antioxidant (KY-405); after coating, the rubber is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm).

[0034] Comparative Example 1

[0035] A comparative rubber-type lithium battery pressure-sensitive adhesive tape is prepared by:

[0036] (1) polycarbonate diol and N-methyl pyrrolidone are mixed to form a mixture, wherein the mixing ratio of the polycarbonate diol and the N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 5 g / 100 mL; the mixture is stirred, and epichlorohydrin is added to the mixture under stirring. After the addition is completed, the mixture is kept in a water bath at a constant temperature of 50±3° C., and after the temperature reaches 50±3° C., boron trifluoride etherate is added to the mixture, and the mixture is kept incubated for 120 minutes. After the incubation is completed, a sodium hydroxide solution is added to the mixture, and the concentration of the sodium hydroxide solution is 40 g / L, the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 5g; continue to keep warm in a water bath at 50±3°C for 120min, then air cool to room temperature, extract with ethyl acetate, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; wherein the mass ratio of the epichlorohydrin and boron trifluoride ether added to the polycarbonate diol is epichlorohydrin: boron trifluoride ether: polycarbonate diol = 12g: 0.05g: 5g;

[0037] (2) The natural rubber is plasticized in an open mixing mill, and after plasticization, it is chopped and dissolved in toluene, and then the cross-linking agent A and the antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, cross-linking agent A and the antioxidant after plasticization in the coating liquid are calculated by weight as follows: 100 parts of rubber, 1.3 parts of cross-linking agent A and 4 parts of antioxidant (KY-405); after coating, it is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm) described in this comparative example.

[0038] Comparative Example 2

[0039] A comparative rubber-type lithium battery pressure-sensitive adhesive tape is prepared by:

[0040] (1) Toluene diisocyanate trimer and acetone are mixed to form a mixed solution, wherein the mass ratio of toluene diisocyanate trimer to acetone in the mixed solution is toluene diisocyanate trimer: acetone = 9:150; polyethylene glycol monomethyl ether is added to the mixed solution, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for 2 hours, and then methyl ethyl ketone oxime is added to the mixed solution, wherein the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 5:1:9; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for 3 hours, and then the mixed solution is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is then added dropwise to the mixed solution, and the mixture is stirred, kept warm for 3 hours, and the mixture is cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is added dropwise to the mixed solution, and the mixture is stirred, kept warm for 3 hours, and the mixture is cooled ... The mass ratio of 3-aminopropyltriethoxysilane added dropwise to the mixed solution is 3-aminopropyltriethoxysilane: mixed solution = 7:50; after the addition is completed, the water bath is kept constant at 50±3°C and kept warm for 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture to obtain the crosslinking agent B described in this comparative example; wherein the mass ratio of the added mass of N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol to the mass of the 3-aminopropyltriethoxysilane is N,N-dimethylethanolamine: 1,3-propane sultone: p-methoxyphenol: 3-aminopropyltriethoxysilane = 0.2:0.3:0.04:7;

[0041] (2) The natural rubber is plasticized in an open mixing mill, and after plasticization, it is chopped and dissolved in toluene, and then the cross-linking agent B and the antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. The rubber, cross-linking agent B and antioxidant in the coating liquid are calculated by weight as follows: 100 parts of rubber, 1.3 parts of cross-linking agent B, and 4 parts of antioxidant (KY-405); after coating, it is baked at 130° C. for 2 minutes to obtain the rubber-type lithium battery pressure-sensitive adhesive tape (dry adhesive thickness 10 μm) described in this comparative example.

[0042] Example 5

[0043] According to the requirements of GB / T2792-2014, the peel strength of the adhesive tapes prepared in the above embodiments and comparative examples was tested respectively, and the peeling rate was set to 300 mm / min, and the bonded substrate was stainless steel; the test of high temperature resistance was: the adhesive tapes prepared in the above embodiments and comparative examples were pasted on a stainless steel plate (surface roughness RA0.8 μm), baked in a constant temperature oven at 160°C for a specified time, and then hot-peeled in the oven to observe whether there was any residual adhesive on the stainless steel plate. The results are shown in Table 1.

[0044] Table 1

[0045] Experimental Group Peel strength (N / 25mm) Temperature resistance 160℃ Example 1 8.776 No residual glue after 4 hours, slight residual glue after 4.5 hours Example 2 9.014 No residual glue after 4 hours, slight residual glue after 4.5 hours Example 3 8.957 No residual glue after 4 hours, slight residual glue after 4.5 hours Example 4 8.809 No residual glue after 4 hours, slight residual glue after 4.5 hours Comparative Example 1 5.244 No residual glue after 2 hours, residual glue after 2.5 hours Comparative Example 2 3.929 No residual glue after 1.5 hours, residual glue after 2 hours

[0046] As can be seen from Table 1, the adhesive tape prepared by the method of the present invention has high peel strength and high temperature resistance. This may be mainly because the crosslinking agent A and the crosslinking agent B prepared by the present invention can crosslink with the active groups contained in the natural rubber, thereby changing the molecular structure of the pressure-sensitive adhesive, making the intermolecular force stronger, the cohesive strength higher, and the crosslinking density of the pressure-sensitive adhesive correspondingly increased, thereby improving the peel strength and high temperature resistance of the adhesive tape.

[0047] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A rubber-type lithium battery pressure-sensitive adhesive tape, characterized in that: The preparation method is: (1) Mixing polycarbonate diol and N-methyl pyrrolidone to form a mixture, wherein the mixing ratio of the polycarbonate diol and N-methyl pyrrolidone is polycarbonate diol: N-methyl pyrrolidone = 4-6 g / 100 mL; stirring the mixture, adding epichlorohydrin to the mixture under stirring, and after the addition is completed, placing the mixture in a water bath and keeping the temperature at 50±3° C., and after the temperature reaches 50±3° C., adding boron trifluoride etherate to the mixture, wherein the mass ratio of the added epichlorohydrin and boron trifluoride etherate to the polycarbonate diol is epichlorohydrin: boron trifluoride etherate: polycarbonate diol = 10-14 g: 0.05-0.06g: 4-6g; keep warm for 120-150min after adding the materials, add sodium hydroxide solution to the mixture after the heat preservation, the concentration of the sodium hydroxide solution is 40-50g / L, and the solvent is water; the mass ratio of the amount of the sodium hydroxide solution added to the polycarbonate diol is sodium hydroxide solution: polycarbonate diol = 50mL: 4-6g; continue to keep warm in a 50±3℃ water bath for 120-150min, then air cool to room temperature, add ethyl acetate for extraction, remove the aqueous phase, and then remove the ethyl acetate by rotary evaporation to obtain a crosslinking agent A; (2) Toluene diisocyanate trimer and acetone are mixed to form a mixed liquid, wherein the mass ratio of the toluene diisocyanate trimer to acetone is toluene diisocyanate trimer: acetone = 8-10:150; polyethylene glycol monomethyl ether is added to the mixed liquid, and after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is kept warm for condensation and reflux for more than 2 hours, and then methyl ethyl ketone oxime is added to the mixed liquid, and the mass ratio of the polyethylene glycol monomethyl ether and methyl ethyl ketone oxime to the toluene diisocyanate trimer is polyethylene glycol monomethyl ether: methyl ethyl ketone oxime: toluene diisocyanate trimer = 4-6: 0.8-1.2: 8-10; after the addition is completed, the temperature is kept constant at 60±3°C in a water bath, and the mixture is stirred, kept warm for condensation and reflux for more than 3 hours, and then the mixed liquid is air-cooled to room temperature, and the acetone is removed by rotary evaporation; 3-aminopropyl triethoxysilane is then added dropwise to the mixed liquid, and the mixed liquid is stirred, kept warm for condensation and reflux for more than 3 hours. The mass ratio of 3-aminopropyl triethoxysilane added dropwise is 3-aminopropyl triethoxysilane: mixed solution = 6-9:50; after the addition is completed, the water bath is kept at a constant temperature of 50±3°C and kept warm for more than 40 minutes, and then N,N-dimethylethanolamine and 1,3-propane sultone are added to the mixed solution in sequence, and after the addition is completed, the mixture is stirred and kept warm for more than 60 minutes within a temperature range of 50±3°C, and then p-methoxyphenol is added to the mixture, and the mass ratio of the N,N-dimethylethanolamine, 1,3-propane sultone and p-methoxyphenol added to the 3-aminopropyl triethoxysilane is N,N-dimethylethanolamine: 1,3-propane sultone: p-methoxyphenol: 3-aminopropyl triethoxysilane = 0.15-0.25: 0.3-0.4: 0.03-0.06: 6-9; obtain a crosslinking agent B; (3) The natural rubber is plasticized in an open mill, and after plasticization, the natural rubber is chopped and dissolved in toluene, and then the crosslinking agent A, the crosslinking agent B and the antioxidant are added, stirred evenly, and toluene is added to adjust the viscosity and then coated on a PET film. In the coating liquid, the rubber, the crosslinking agent A, the crosslinking agent B and the antioxidant are calculated by weight as follows: 100 parts of rubber, 1 to 2 parts of crosslinking agent A, 0.2 to 0.4 parts of crosslinking agent B, and 3 to 5 parts of antioxidant; and baked at 130° C. to obtain the rubber-type lithium battery pressure-sensitive adhesive tape.

Citation Information

Patent Citations

  • High-temperature-resistant pressure sensitive adhesive tape and preparation method thereof

    CN105419663A

  • Pressure sensitive adhesive and preparation method thereof and adhesive tape

    CN109486451A